The Impact of Using the Balanced Scorecard in Enhancing Organizational Agility: An Applied Study on Technical Colleges in the Asir Region - Mohammed, Raghad Ali; Al-Dabbabi, Mohsen (Journal of Economic, Administrative and Legal Sciences, 2025)
The aim of the study was to identify the impact of the Balanced Scorecard dimensions on organizational agility and to examine the statistically significant differences in the study sample's perceptions regarding this impact based on variables such as academic qualification, years of service, and job title. The researcher employed the descriptive-analytical method for conducting the study. The research population consisted of 306 administrative employees, of which a simple random sample of 169 administrative staff was selected. A questionnaire was used as the primary research tool, and data were analyzed using the SPSS program. The study revealed several findings: There is a statistically significant impact of the Balanced Scorecard dimensions (financial dimension, customer dimension, internal processes dimension and learning and growth dimension) on enhancing organizational agility in the technical colleges in the Asir region. Furthermore, there are statistically significant differences attributed to the variables of academic qualification and years of service in the average responses of the study sample regarding the Balanced Scorecard. However, no significant differences were found concerning job title. Additionally, there were no statistically significant differences in the perceptions of the sample regarding organizational agility based on academic qualification, years of service, or job title. The study recommended that the management of technical colleges should provide training courses on the dimensions of the Balanced Scorecard and organizational agility to administrative employees across different job titles and should continuously update the Balanced Scorecard to keep pace with future changes in the work environment and technical and educational challenges.
Keywords: Balanced Scorecard; Organizational Agility; Technical Colleges in Asir Region